Bilvapatra Treasures of Indian Art - Giri, Kamal (ed); Tiwari, M. N. P. (ed); Joshi, N. P. (New Delhi Research India Press Publications, 2013)
A Unique Stone Sculpture of Dhanvantari From the Russek Collection